Visceral adiposity index is associated with benign prostatic enlargement in non-diabetic patients: a cross-sectional study. (2nd January 2018) - Besiroglu, Huseyin; Ozbek, Emin; Dursun, Murat; Otunctemur, Alper
Abstract: Objective: To evaluate the association between visceral adiposity index (VAI) - a novel indicator for the assessment of visceral adipose tissue and prostate enlargement in non diabetic patients. Material and methods: Four hundred patients who were admitted to the Urology clinic between January and December 2014 with complaints of BPH(benign prostatic hyperplasia )/LUTS(male lower urinary tract symptoms)were enrolled in this cross-sectional study. Patients were divided into two groups according to their prostate volume and international prostate symptom score (IPSS) value. They were compared in terms of age, body mass index (BMI), VAI, prostate volume, PSA, post micturional residual volume (PMRV), uroflowmetry Q max value, triglyceride (TG), high density lipoprotein-cholesterol (HDL-C) and fasting blood sugar (FBS). Results: Although univariate analyses reveal that age, BMI, waist circumference (WC), FBS, TG, HDL-C level and TG/HDL ratio were correlated with prostate volume, only age [1.125 OR (1.088–1.164), p  = .00001], BMI [1.119 OR (1.040–1.204), p  = .003], TG [1.043 OR (1.016–1.071), p  = .002], HDL-C [0.923 OR (0.860–0.990), p  = .025] and VAI [1.194 OR (1.110–1.305), p  = .011] were statistically significant in multivariate analysis. A positive correlation was found between VAI value and prostate volume in the Spearman correlation test ( r  = 0.29, p  = .00001). The calculated area under the curve (AUC) for prostate volumes of 30, 40 and 50 ml were 0.680 (0.621–0.738), 0.625 (0.570–0.681) and 0.590 (0.528–0.652), respectively. Conclusion: Our study revealed a positive correlation between VAI and prostate volume. Our results are needed to be tested with well-designed randomized prospective cohort studies.